Effect of a magnetic field on dispersion of a hop extract and the influence on gushing of beer. (January 2015) - Shokribousjein, Zahra; Galan, David Riveros; Michiels, Chris; Gebruers, Kurt; Verachtert, Hubert; Martens, Johan; Peeters, Christine; Derdelinckx, Guy
Highlights: We characterised a hop extract antifoam to be used in brewing industry to reduce gushing of beer. We examine the influence of a magnetic field on dispersion of the hop extract. Magnetic field decreased the sizes of hop extract and inhibited gushing more. By using the magnet, hop extract should be used in low amount to avoid higher gushing. For a better result, the hop extract needs pretreatment by magnetic field before adding to wort. Abstract: Hydrophobins are surface active molecules that cause gushing of beer. Gushing is vigorous overfoaming of carbonated beverages without any shaking. A hop extract was used to decrease gushing of wort induced by hydrophobin HFBI. The influence of a magnetic field on dispersion of the hop extract was used to decrease gushing by HFBI. The results indicate that when a magnetic field exerted on hop extract, this compound is dispersed more and smaller particles are formed. Therefore, the specific surface areas of the particles are increased and interact with larger numbers of hydrophobins. This resulted in less gushing by HFBI. When hydrophobins and hop extract together were submitted to magnetic field more gushing was obtained than in the absence of magnet. This is due to the extensive dispersion of the combination by the magnet and can be limited by using less amount of hop extract.